DESIGN AND TESTING TEMPERATURE CONTROLLER SYSTEM OF DOME PARABOLA SOLAR DRYER - Bunmephiphit, Chanon; Chulapak, Weerasak (Life Sciences and Environment Journal, 2021)
The drying process using solar radiation as an energy source causes uncontrollable temperature, due to the inability to control the amount of solar radiation. The drying temperature is unstable and directly affects the drying results of various products. Therefore, the objectives of this research were 1) to study and design the drying process by using a greenhouse effect solar oven with the temperature control system, and 2) to compare the temperature control efficiency between the oven with temperature control system and without temperature control system. Results showed that the automatic temperature control system with convection technique between the two oven walls can control the temperature and has a maximum banana drying volume of 30 kg per time. The temperature control efficiency of the greenhouse solar dryer is 96.5%.